Letramento Crítico, Representatividade E Ensino De Língua Inglesa No Pibib (PERcursos Linguísticos, 2021)
This paper aims to report and reflect on an English lesson whose theme was the representation of black women in society. Based on the reading and discussion of texts, in the scope of PIBID, about Critical Literacy in the teaching of English, the referred lesson was planned and taught to an 8th graders group, in a municipal school in João Pessoa - PB. In order to promote with the students the development of critical reading about their own reality, the lesson was divided into three moments. In the first one, the reading of multimodal texts about a movie that addresses the intended theme. In the second one, the discussion about the representation of black women and other underprivileged minorities. In the third one, the production of posters and blurbs about a fictional movie, which would also address issues of representativeness. This sequence of activities allowed students to reflect on the different realities where they live, once other relevant themes were addressed during the lesson. In this way, we argue that the promotion of Critical Literacy allows the perception and the analysis of topics that are relevant for students, which can be an instrument for their citizenship.